Collaborating for (Game) Change(rs): Negotiating and Building Meaningful Action Research Partnerships - Barrett, Joe; Robinson, Daniel B.; Walters, William (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2024)
Sport- and physical activity-related participatory action research (PAR) often involves voluntary partnerships spanning institutions, organizations, and jurisdictions. Negotiating and maintaining multi-stakeholder and multi-jurisdictional research partnerships can be likened to a delicate balancing act fraught with potential challenges and strains impacting project outcomes (e.g., waning commitment, emerging external factors, new and/or revised stakeholder/organizational requirements, fidelity to the necessary care given when working with community partners and participants). This article presents PAR as a methodology in sport and physical activity that can potentially engage all research participants as co-researchers, sharing power equitably. Recognizing the need for continued attention and action in this area, we provide an overview of PAR in practice, identifying significant ideas and principles. Additionally, we outline Game Changers—a PAR project involving students with various disabilities, schools, PE teachers, coaches, national and community sport partners, and university researchers. Based on lessons learned from this multi-stakeholder and multi-jurisdictional research project, we interrogate the possibilities associated with engaging in PAR by exploring challenges and opportunities related to sport and physical activity-focused PAR.